Sports nutrition (The encyclopaedia of sports medicine, XIX, 2014)
It is well understood that proper nutrition has a significant impact on sports performance. All of the essential nutrients must be supplied in the right amounts and at the right times for an athlete to achieve optimal health and performance. In addition, when devising eating strategies that will help athletes meet their goals, sports nutritionists must take account of personal preferences, social and cultural issues, and a whole range of other factors.